30 Rock - Season 4 Episode 1-22 - Scardino, Don; Mancuso, Gail; MacCarthy-Miller, Beth; Clark, Matthew; Fey, Tina; Baldwin, Alec; Morgan, Tracy (Universal Pictures, 2016)
Liz Lemon, (Tina Fey) is the head writer on a variety series on NBC Studios. With the Jack Donaghy as Vice President of East Coast Television, played by Alec Baldwin, Series four sustains the same standard that has maintained it so far with plenty of exceptional moments. The characters are still all hugely dysfunctional and written with enormous affection and comic effect. The situations beautifully constructed. This set contains all the episodes from the show’s fourth series. [www.amazon.co.uk]